ANALISIS POTENSI RETRIBUSI RUMAH POTONG HEWAN PADA UPACARA RAMBU SOLO’ DAN RAMBU TUKA’ DI KABUPATEN TORAJA UTARA - Silamba, Regina Sheren; Kalangi, Lintje; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2017)
The area retribution is one of locally generated revenue. Retribution is compulsory payments of the people to the state due to the existence of certain services provided by the state for its individual population. Toraja cultural activities are still very actively conducted by the people, where every traditional ceremony involves slaughterhouses, which means the collection of retribution slaughterhouses. This research aims to find out the potential of Retribution of Slaughterhouses ini Toraja Utara District. The data used is the primary data sourced from the interview and the secondary data sourced from the realization of retribution of slaughterhouse in 2013-2016. The analysis taken is potency of slaughterhouse retribution analysis. The results of the analysis show that the livestock slaughterhouse abattoir outside the slaughterhouse is bigger than the slaughterhouse. The analysis show that at the ceremony Rambu Solo’ and Rambu Tuka’, Pudu buffalo and pigs have great potential in retribution collection. This is because in Toraja customs, animal slaughter is not done carelessly.Keywords: Potential, Retribution of Slaughterhouse.